European Yearbook of International Economic Law 2012
XVIII, 718 p. 14 illus.
Keywords: The third volume of the European Yearbook of International Economic law focuses on two major topics of current academic and political interest. Firstly, it adresses the 10th anniversary of China's accession to the WTO and its implications; secondly, it deals with different legal aspects of global energy markets.